The Educational Contribution of an Aesthetic of Andeanness: Considerations on a Recent Philosophical and Literary Research Study - Martin de Blassi, Fernando G. (Rastros Rostros, 2016)
Aim: This article seeks to critically reflect on the issues and ideas proposed by Liliana Mannina de Gamero inAndean Silence: Marker of Identity .Towards an aesthetic of Andeanness.  Description: Priority is given to a methodology of hermeneutics, which consists of interpreting selected texts in order to analyze them. These texts were selected in an attempt to uncover the various levels of understanding articulated in the study by Mannina de Gamero, the questions she poses, and the issues that arise as a result of this questioning. Point of view: The aesthetic of the author is established through a critical analysis of the humanistic contributions of three Argentinian poets: Juan Draghi Lucero, Manuel J. Castilla, and Héctor D. Gatica. This article is not limited to a specialized audience but rather seeks to stimulate the pleasurable reading of these three poets. Conclusions: The approach developed by Mannina de Gamero about the aesthetic of Andeanness contributes to the reassessment, on the conceptual basis of the relationship between writing poetry and thinking, of the existential question of identity and historical recognition presupposed by every educational phenomenon in Latin America.
Keywords: aesthetic of Andeanness; identity; recognition; silence